The durability of modified silica/polypropylene nanocomposites : weathering resistance and creep behavior - Anis Sofiah Mudzafar Kamil (School of Materials Engineering, Universiti Malaysia Perlis, 2014)
In this research, the modified silica (SiO2)/polypropylene (PP) nanocomposites were prepared. The accelerated weathering and creep behavior of nanocomposites were investigated.